From research to daily clinical practice: implementation of orthogeriatric co-management in the trauma ward - Janssens, Sigrid; Deschodt, Mieke; Dejaeger, Marian; Fagard, Katleen; Cerulus, Marie; Cosyns, Heidi; Flamaing, Johan; Herteleer, Michiel; Sermon, An (Frontiers in Health Services, 2023)
Introduction: Evidence strongly suggests that orthogeriatric co-management improves patient outcomes in frail older patients with a fracture, but evidence regarding how to implement this model of care in daily clinical practice is scarce. In this paper, we first describe the implementation process and selection of implementation strategies for an orthogeriatric co-management program in the traumatology ward of the University Hospitals Leuven in Belgium. Second, we report the results of a multi-method feasibility study. This study 1) measures the fidelity towards the program’s core components, 2) quantifies the perceived feasibility and acceptability by the healthcare professionals, and 3) defines implementation determinants. Methods: Implementation strategies were operationalized based on the Expert Recommendations for Implementing Change (ERIC) guidelines. In the feasibility study, fidelity towards the core components of the program was measured in a group of 15 patients aged 75 years and over by using electronic health records. Feasibility and acceptability as perceived by the involved healthcare professionals was measured using a 15-question survey with a 5-point Likert scale. Implementation determinants were mapped thematically based on seven focus group discussions and two semi-structured interviews by focusing on the healthcare professionals’ experiences. Results: We observed low fidelity towards completion of a screening questionnaire to map the premorbid situation (13%), but high fidelity towards the other program core components: multidimensional evaluation (100%), development of an individual care plan (100%), and systematic follow-up (80%). Of the 50 survey respondents, 94% accepted the program and 62% perceived it as feasible. Important implementation determinants were feasibility, awareness and familiarity, and improved communication between healthcare professionals that positively influenced program adherence. Conclusions: Fidelity, acceptability, and feasibility of an orthogeriatric co-management program were high as a result of an iterative process of selecting implementation strategies with intensive stakeholder involvement from the beginning.